Pengaruh Defisit Anggaran, Inflasi dan Nilai Tukar Rupiah Terhadap Utang Luar Negeri Indonesia dalam Perspektif Ekonomi Islam Tahun 2010-2019 - Fauzi Fauzi; Muhammad Suhaidi (ITB AAS INDONESIA Surakarta, 2022)
This research aims to analyze the effect of the budget deficit, inflation and rupiah exchange rate on Indonesia's foreign debt in 2010-2019 partially and simultaneously and reviewed from the perspective of Islamic economics. The object of this research is Indonesia's foreign debt as the dependent variable, and three independent variables, namely the budget deficit, inflation and the rupiah exchange rate from 2010 to 2019. This research is a quantitative research. The type of data used is secondary time series data from 2010-2019 which was obtained from the official website of Bank Indonesia, the Ministry of Finance of the Republic of Indonesia and the Indonesian Central Statistics Agency. Data collection techniques in this research are documentation and literature study. The population in this study is all data on Indonesia's foreign debt, budget deficit, inflation and the rupiah exchange rate. The sample in this study is data on Indonesia's foreign debt, budget deficit, inflation and the rupiah exchange rate for 2010-2019. The sampling technique in this study used purposive sampling. Analysis of the data used is multiple linear regression analysis in OLS (Ordinary Least Square) using the computer program E-views 9. The results showed that partially the budget deficit had no positive and insignificant effect on Indonesia's foreign debt. Inflation has no positive and insignificant effect on Indonesia's foreign debt. The rupiah exchange rate has a positive and significant effect on Indonesia's foreign debt. The results of the study show that the budget deficit, inflation and the rupiah exchange rate together have a significant effect on Indonesia's foreign debt in 2010-2019. Foreign debt is actually allowed in Islam, but it is not recommended, external financing (funds from outside) is allowed as long as the mechanism is modified according to Islamic law.